BioFire FilmArray Decreases Infection Control Isolation Times by 4 days in ICU, BMT and Respiratory Wards. (4th October 2017) - Wong, Titus; Stefanovic, Aleksandra; Locher, Kerstin; Bryce, Elizabeth; Grant, Jennifer M; Connolly, Eithne; Woznow, Tracey; Charles, Marthe; Hoang, Linda Mn; Jassem, Agatha; Roscoe, Diane
Abstract: Background: Novel, rapid, syndromic testing of patients presenting with respiratory infections has the potential to improve patient access and care by decreasing time to diagnosis. BioFire FilmArray (BioFire Diagnostics, bioMerieux) is a cartridge-based, multiplex PCR platform capable of detecting 17 viral and 3 bacterial targets in one hour. This study assessed the impact of implementing this technology on the duration of infection control isolation. Methods: A randomized control trial in a 900-bed tertiary-care academic hospital was conducted between December 2016 and January 2017. Fifty consecutive samples of patients with respiratory infections on our ICU, BMT and Respiratory wards to received either BioFire FilmArray Respiratory Panel (BF) diagnostic testing or our routine diagnostic testing (RO) consisting of an influenza A/B/RSV PCR (in-house) followed by Luminex NxTag Respiratory Pathogen Panel that was batched at a reference lab. Five patient charts with missing data were excluded from analysis. Statistical analysis was completed using RStudio Version 1.0.136 – © 2009–2016 RStudio, Inc. Results: Patients randomized to the BF arm remained on respiratory isolation precautions on average (42.3 ± 72.9 hours) over 100 hours less than patients randomized to the routine arm (151.3 ± 151.8 hours) (95% CI: 35.6–184.4 hours, P = 0.0052). Conclusion: Implementing the BioFire FilmArray Respiratory Panel decreased infection control isolation time by approximately 4 days compared with routine testing; further study is warranted to determine the impact of this technology on patient outcomes and cost benefit. Disclosures: T. Wong, bioMerieux: Investigator, Research grant A. Stefanovic, bioMerieux: Investigator, Research grant E. Bryce, bioMerieux: Investigator, Research grant J. M. Grant, bioMerieux: Investigator, Research grant D. Roscoe, bioMerieux: Investigator, Research grant